Evaluation of disaster safe education unit programme implementation in Mt. Merapi using the pressure state response approach - Puspita I. Wardhani; Muhammad Musiyam; Yunus A. Wibowo; Aries Dwi W. Rahmadana; Sri Utami; Edwin Maulana (Jàmbá, 2024)
Disaster Safe Education Unit (SPAB), also known globally as Comprehensive Safe School (CSS), aims to improve school residents’ resilience. Three pillars of SPAB have been established, but their implementation, to date, has not shown satisfactory results. This study aims to evaluate the implementation of the SPAB programme in the disaster-prone area (KRB) of Merapi Vulcano in Sleman, Yogyakarta, Indonesia. Data collection was conducted using a field survey combined with in-depth interviews. Overall, the study focussed on the 32 schools in the KRB Merapi. The SPAB implementation was evaluated by considering the Pressure-State-Response (PSR) indicator. The study results showed that not all schools in KRB Merapi implemented the SPAB programme. Safe schools have not fully implemented the three pillars of SPAB. Pillar 3 had the highest rate (96.40%) of implementation in safe schools, whereas Pillar 1 had the lowest (54.5%). Legality, funding and human resources are the critical plausible explanations for why the SPAB pillars have not been implemented well. These problems affect school infrastructure, the capacity of educators, consistency and school motivation in implementing SPAB programme.